Women’s Language Features and Narcissistic Self-Presentation: A Sociopragmatic Analysis of Q&A Interactions in Gus Iqdam’s Religious Forum - Rosita Ambarwati; Heny Kusuma Widyaningrum; Enhelyn Llaneza Morla; Rara Risma Gressilya (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2026)
This study examines women’s language features and micro-narcissistic self-presentation in digitally mediated religious discourse, focusing on question-and-answer (Q&A) interactions in the online “Pengajian Sabilu Taubah” led by Gus Iqdam. Adopting a qualitative descriptive design with a sociopragmatic orientation, the study aims to explore how female participants use language to negotiate emotion, politeness, authority, and self-visibility in a publicly streamed religious forum. The data were drawn from five publicly accessible livestream recordings and were selected through purposive sampling based on the presence of direct interaction with female participants, extended utterances, and adequate audio-visual quality. Three women participants were analyzed as primary data sources, while two additional participants were used for confirmatory analysis. The primary research instrument was detailed discourse transcription, including lexical, prosodic, and paralinguistic features. Data analysis followed a theory-driven qualitative content analysis guided by Lakoff’s framework of women’s language and Pearson’s functional classification, with data validation ensured through triangulation and confirmatory analysis. The findings show that women’s language in the Q&A sessions is characterized by expressive-affective features, mitigation strategies, and response-oriented utterances that function to elicit recognition and maintain politeness toward religious authority. Furthermore, micro-narcissistic self-presentation is realized through subtle and socially acceptable linguistic practices, such as admiration-seeking expressions and self-referential narratives, rather than overt self-promotion. This study contributes to sociopragmatic and gender-based discourse research by highlighting women’s linguistic agency in digital religious interaction and by conceptualizing micro-narcissism as an interactional phenomenon shaped by religious norms and public visibility.